If f: A → B, g: B → C
Then
gof : A → C
gof = g(f(x))
Here, gof is formed by the composition of functions f and g.
In gof :
- Value of x is coming from set A
- Value of function gof will be from set C
Let us take an example
Let f: {1, 2, 3, 4} → {5, 6, 7, 8}
f(1) = 5, f(2) = 6, f(3) = 7, f(4) = 8
and
g: {5, 6, 7, 8} → {9, 10, 11, 12}
g(5) = 9, g(6) = 10, g(7) = 11, g(8) = 12
Find gof
gof will be
gof (1) = 10
gof (2) = 11
gof (3) = 12
gof (4) = 13
Let’s take another example
f: R → R , g: R → R
f(x) = sin x , g(x) = x 3
Find fog and gof
f(x) = sin x
f(g(x)) = sin g(x)
f og (x) = sin (x 3 )
g(x) = x 3
g(f(x)) = f(x) 3
go f (x) = sin 3 x
Note that go f ≠ f og .